Electromyographic validation of basic exercises for physical conditioning programmes: II. Analysis of the deltoid muscle (anterior portion) and pectoralis major muscle (clavicular portion) in rowing exercises with closed grip - Ferreira, M. I.; Vitti, M. [UNESP]; Büll, M. L. [UNESP] (My University, 1996)
The electromyographic activity of the shoulder muscles deltoid-anterior portion (DA) and pectoralis major-clavicular portion (PMC) was tested on 24 male volunteers using a 2 channel TECA TE4 electromyograph and Hewlett Packard surface electrodes during the execution of three different modalities of rowing exercises with closed grip. All rowing exercises were inefficient to determine action potential levels in the PMC but two of them were extremely efficient to the DA: the upright rowing exercise and the sitting rowing exercise. Some suggestions to the use of the tested exercises are presented by the authors.